Automated irrigation system using sensors and node micro controller unit - Sai Teja, P. Shanmukha; Vineel, M.; Manisha, G.; Satyanarayana, S. (International Journal of Engineering and Technology, 2017)
Internet of things IOT is a network of systems connected within the systems, systems or devices like smart phones, sensors, computer. Internet of things connects all the surrounding devices to internet that is internet of things. Smart devices is an electronic device that can take logical and intelligent decisions on its own. Sensor are small chip that reacts to the sensed activities. Transfer of data is also done in IOT the data which is taken from sensors is sent through cloud database and again can be retreated for the necessary response. The medium of both smart device and database is internet. In this project main motto is to record the changes and information of agriculture field. This makes the easy way to cultivate the field in protective shield. Here we get the details of soil moisture, temperature, humidity, and periodic information of water supply to field. In agriculture water is the main source to a good healthy field. This project helps us to make use of water in efficiently in agriculture fields. Also farmer ids safe from many incoming dangers like thunder strike, snake bite and so on. Introducing technology to farmer to operate his field through his phone. This IOT project helps the farmer to collect the information about water level, soil moisture, humidity, soil fertility, and monitoring of crop allows to find weed, pest detection, animal entry into field, and growth of crop. Arduino is an open and free source hardware model used to dump software. It reads input signals of sensors and in response the output activation of things like motor, light. Sensors which senses the variation in different mediums of atmosphere inputs analogue to digital outputs. Think speak is open source cloud can store and retrieve data of sensors by local area network.